Respuesta :

Answer:

(x, y ) = (- 2, 3 )

Step-by-step explanation:

given the 2 equations

7x - 2y = - 20 → (1)

9x + 4y = - 6 → (2)

multiply (1) by 2 making the coefficients of y equal and opposite

14x - 4y = - 40 → (3)

add (2) and (3) term by term

(9x + 14x ) + (4y - 4y ) = (- 6 - 40 )

23x = - 46 ( divide both sides by 23 )

x = - 2

substitute x = - 2 into either (1) or (2) for y

(2) - 18 + 4y = - 6 ( add 18 to both sides )

4y = 12 ( divide both sides by 4 )

y = 3

solution is (- 2, 3 )


Answer:

The answer would be well, B.(-2,3)